2018
DOI: 10.1109/tnnls.2017.2657601
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Spiking Neural Network for Virtual Screening

Abstract: Virtual screening (VS) has become a key computational tool in early drug design and screening performance is of high relevance due to the large volume of data that must be processed to identify molecules with the sought activity-related pattern. At the same time, the hardware implementations of spiking neural networks (SNNs) arise as an emerging computing technique that can be applied to parallelize processes that normally present a high cost in terms of computing time and power. Consequently, SNN represents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…21 SNNs have a wide application potential. Modern interesting applications of SNN include, e.g., epilepsy examination, [22][23][24] medical diagnostics, 25 pattern recognition, 26,27 neurosurgery, 28 information processing, 29 and liquid-state machine circuitry. 30 SN P systems have some common features with SNNs: a neuron fires only when its potential or the number of spikes inside it reaches a specific value; the concept of time is incorporated into the information encoding and processing.…”
Section: Introductionmentioning
confidence: 99%
“…21 SNNs have a wide application potential. Modern interesting applications of SNN include, e.g., epilepsy examination, [22][23][24] medical diagnostics, 25 pattern recognition, 26,27 neurosurgery, 28 information processing, 29 and liquid-state machine circuitry. 30 SN P systems have some common features with SNNs: a neuron fires only when its potential or the number of spikes inside it reaches a specific value; the concept of time is incorporated into the information encoding and processing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the multi-threaded design of the webserver and alignment-free nature of USR method also contributed to such a high computational efficiency. A hardware implementation of USR has been shown to achieve two-fold speed gains over standard CPU based implementation of USR (Morro et al, 2018 ). In this implementation, a computing technique, Spiking Neural Networks, has been adapted utilizing Field-Programmable Gate arrays to allow highly parallelized implementation of USR.…”
Section: D Shape Similarity Methodsmentioning
confidence: 99%
“…(c) Another three dimensional implementation with a layer dedicated to memory and another to the computing elements. Crossbar arrays and three-dimensional circuits are not the only trail of hardware improvement. For example, Morro et al [128] have reported replacing a part of their ASIC, initially designed with traditional digital gates, by neuromorphic hardware. This sort of mixed neuromorphic integration is probably relevant for other applications.…”
Section: Hardware Implementationsmentioning
confidence: 99%